A qualitative study: the challenges on anti parasitic infection campaign among Orang Asli from the perspective of Tok Batin & JAKAO officer in Maran, Pekan and Kuantan, Pahang - Normalina A,; Mohamad Helmy Jaafar,; Muhammad Lokman Md Isa, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2022)
The issue of parasitic intestinal infections among indigenous people is often discussed. Nevertheless, there is no end to this issue. Therefore, information from authorised parties or personnel such as JAKOA and Tok Batin which involve in the indigenous people is important in order to overcome this issue. This study is important in improving the quality of life of the indigenous. Therefore, the objectives of this study were; (i) to explore the problems faced by the authority related to parasitic infections among Orang Asli in Kuantan, Maran and Pekan, Pahang; and (ii) to identify the perceptions of the authority about the problem related to parasitic infections among Orang Asli in Kuantan, Maran, and Pekan, Pahang. This was a qualitative cross-sectional study. Interviews were conducted on six eligible key informants based on criteria in the selected areas in Kuantan, Maran and Pekan, Pahang. This study used thematic analysis to analyse the data. The identified problems from the perspectives of authorized personnel were; (i) hygienic issue; (ii) improper solid waste management; and (iii) inadequate clean water supply. Current findings recommended strategies which were; (i) to conduct awareness program; (ii) to conduct social program; (iii) provides proper waste disposal landfills; and (iv) to provide adequate clean water supply. Research findings and strategy recommendations need to be prioritized by the government for the purpose of improvement Furthermore, the government should also review all current programs to determine its effectiveness towards the Orang Asli community.